Fracture healing: A review of clinical, imaging and laboratory diagnostic options. (June 2017) - Cunningham, Brian P.; Brazina, Sloane; Morshed, Saam; Miclau, Theodore
Abstract: A fundamental issue in clinical orthopaedics is the determination of when a fracture is united. However, there are no established "gold standards, " nor standardized methods for assessing union, which has resulted in significant disagreement among orthopaedic surgeons in both clinical practice and research. A great deal of investigative work has been directed to addressing this problem, with a number of exciting new techniques described. This review provides a brief summary of the burden of nonunion fractures and addresses some of the challenges related to the assessment of fracture healing. The tools currently available to determine union are discussed, including various imaging modalities, biomechanical testing methods, and laboratory and clinical assessments. The evaluation of fracture healing in the setting of both patient care and clinical research is integral to the orthopaedic practice. Weighted integration of several available metrics must be considered to create a composite outcome measure of patient prognosis.